Social Spending for Inclusive Growth in the Middle East and Central Asia - Mathai, Koshy (International Monetary Fund, 2020)
This paper examines the role of social spending in improving socioeconomic outcomes in the Middle East and Central Asia. In particular, it addresses the following questions: (1) how large is social spending across the region? (2) how do countries in the region fare on socioeconomic outcomes? (3) how important is social spending as a determinant of these outcomes? and (4) how efficient is social spending in the region?